2020
DOI: 10.1126/sciadv.aax9361
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell geochemistry reveals ancestral metabolic thermoregulation in Dinosauria

Abstract: Studying the origin of avian thermoregulation is complicated by a lack of reliable methods for measuring body temperatures in extinct dinosaurs. Evidence from bone histology and stableisotopes often relies on uncertain assumptions about the relationship between growth rate and body temperature, or the isotopic composition (δ18O) of body water. Clumped isotope (Δ47) paleothermometry, based on binding of 13C to 18O, provides a more robust tool, but has yet to be applied across a broad phylogenetic range of dinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 68 publications
6
41
0
Order By: Relevance
“…It is clear that the average of the estimated body temperatures is close to that of the modern mammals. However, there is a large fluctuation, which probably indicates variable thermoregulation between and among the different species, a conclusion consistent with a recent study of dinosaur eggshells ( Eagle et al., 2015 ; Dawson et al., 2020 ). It is also possible that some of the dinosaur species regulated their body temperatures to some extent by altered behaviour, while some others could maintain theirs like modern endotherms ( Dawson et al., 2020 ).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…It is clear that the average of the estimated body temperatures is close to that of the modern mammals. However, there is a large fluctuation, which probably indicates variable thermoregulation between and among the different species, a conclusion consistent with a recent study of dinosaur eggshells ( Eagle et al., 2015 ; Dawson et al., 2020 ). It is also possible that some of the dinosaur species regulated their body temperatures to some extent by altered behaviour, while some others could maintain theirs like modern endotherms ( Dawson et al., 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…A few researchers have shown that the clumped isotope thermometry can be used to estimate the body temperature of oviparous animals using the eggshell carbonates (e.g., Wacker et al., 2014 ; Eagle et al., 2015 ; Dawson et al., 2020 ). To confirm the applicability of this thermometer to infer the oviduct temperature of egg laying animals, we analysed eggshells of modern birds and reptiles including snakes and crocodiles collected from two Taiwan zoos.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations